LEARNING BY BEING OR ASSUMPTION OF COGNITIVE GOALS - Mihail CALALB (Moldova State University, 2020)
The analysis of the recent evolution of educational paradigms is made and the new approach of Learning by being is presented in this work. A series of teaching and learning approaches are discussed from the point of view of Visible Teaching and Learning (VTL) theory. The role and the place of student's personal learning effort within several teaching strategies, which have a significant impact on academic achievement of students, is analysed. In this context, the author presents his concept of guided self-scaffolding and emphasises that at least three student-related moments should be presented in each constructivist teaching strategy: student's personal effort, mutual feedback and metacognition. Also, such learning approaches like information structuring, recurrent use of information or help seeking are analysed in relation with Learning by being concept.   ÎNVĂȚAREA PRIN A FI SAU ASUMAREA OBIECTIVELOR COGNITIVE Este efectuată analiza evoluției recente a paradigmelor educaționale și este prezentată o nouă abordare, denumită Învățarea prin a fi (Learning by being). O serie de strategii de predare și învățare este analizată din punctul de vedere al teoriei Predării și Învățării Vizibile (Visible Teaching and Learning). Este analizat rolul și locul efortului personal al elevului în cadrul unor strategii didactice, care au un impact semnificativ asupra succesului academic al elevilor. În acest context, autorul prezintă conceptul său de autoînvățare ghidată (guided self-scaffolding) și subliniază că cel puțin trei momente legate de elev ar trebui să fie prezente în fiecare strategie de predare constructivistă: efortul personal al elevului, legătura inversă reciprocă și metacogniția. De asemenea, astfel de strategii de învățare ca structurarea informației, folosirea recurentă a informației, cererea ajutorului sunt analizate în contextul conceptului de Învățare prin a fi.